Validity and Reliability of the Persian Version of the Dysphagia Handicap Index (DHI) - Asadollahpour, Faezeh (Iran J Otorhinolaryngol, 2015)
INTRODUCTION: The Dysphagia Handicap Index (DHI) is one of the instruments used for measuring a dysphagic patient’s self-assessment. In some ways, it reflects the patient’s quality of life. Although it has been recognized and widely applied in English speaking populations, it has not been used in its present forms in Persian speaking countries. The purpose of this study was to adapt a Persian version of the DHI and to evaluate its validity, consistency, and reliability in the Persian population with oropharyngeal dysphagia. MATERIALS AND METHODS: Some stages for cross-cultural adaptation were performed, which consisted in translation, synthesis, back translation, review by an expert committee, and final proof reading. The generated Persian DHI was administered to 85 patients with oropharyngeal dysphagia and 89 control subjects at Zahedan city between May 2013 and August 2013. The patients and control subjects answered the same questionnaire 2 weeks later to verify the test-retest reliability. Internal consistency and test-retest reliability were evaluated. The results of the patients and the control group were compared. RESULTS: The Persian DHI showed good internal consistency (Cronbach’s alpha coefficients range from 0.82 to 0.94). Also, good test-retest reliability was found for the total scores of the Persian DHI (r=0.89). There was a significant difference between the DHI scores of the control group and those of the oropharyngeal dysphagia group (P‹0.001). CONCLUSION: The Persian version of the DHI achieved Face and translation validity. This study demonstrated that the Persian DHI is a valid tool for self-assessment of the handicapping effects of dysphagia on the physical, functional, and emotional aspects of patient life and can be a useful tool for screening and treatment planning for the Persian-speaking dysphagic patients, regardless of the cause or the severity of the dysphagia.